2023
DOI: 10.14512/gaia.32.s1.5
|View full text |Cite
|
Sign up to set email alerts
|

Digitalization and sustainability: A systematic literature analysis of ICT for Sustainability research

Abstract: Close scrutiny of the ICT for Sustainability conference proceedings on digitalization and sustainability reveals a bias on (technological) efficiency solutions. This bias is mirrored in blind spots in the public discourse and the political debate. The sustainable transformation of society calls for more comprehensive research ‐ and research funding ‐ to fill the gaps and integrate efficiency, consistency, and sufficiency strategies on the levels of life-cycle, enabling, and structural effects.In order to gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…For example, one study reports that 58% of their examined studies focus exclusively on the positive effects, while only 15% analyzed focused on negative effects [9]; another review found 52% of papers in their sample that describe ICT solutions as enabler [28]. Different enablement scenarios are mentioned in the analyzed reviews, for example, promoting renewable energy, driving energy efficiency [7,8,28], ensuring pollution and waste control that help create smart cities [8], managing energy demand and supply [8,28], platforms for helping establish a circular economy [29], promoting sustainable mobility [27], or enabling education for sustainability [19]. However, there is little research on how ICT-based solutions can enable deep sustainability transformations, such as supporting the move to more sustainable agriculture [28].…”
Section: De Uplication #And" !$ "! ! Ynthesize Fin Ings An Gapsmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, one study reports that 58% of their examined studies focus exclusively on the positive effects, while only 15% analyzed focused on negative effects [9]; another review found 52% of papers in their sample that describe ICT solutions as enabler [28]. Different enablement scenarios are mentioned in the analyzed reviews, for example, promoting renewable energy, driving energy efficiency [7,8,28], ensuring pollution and waste control that help create smart cities [8], managing energy demand and supply [8,28], platforms for helping establish a circular economy [29], promoting sustainable mobility [27], or enabling education for sustainability [19]. However, there is little research on how ICT-based solutions can enable deep sustainability transformations, such as supporting the move to more sustainable agriculture [28].…”
Section: De Uplication #And" !$ "! ! Ynthesize Fin Ings An Gapsmentioning
confidence: 99%
“…Different enablement scenarios are mentioned in the analyzed reviews, for example, promoting renewable energy, driving energy efficiency [7,8,28], ensuring pollution and waste control that help create smart cities [8], managing energy demand and supply [8,28], platforms for helping establish a circular economy [29], promoting sustainable mobility [27], or enabling education for sustainability [19]. However, there is little research on how ICT-based solutions can enable deep sustainability transformations, such as supporting the move to more sustainable agriculture [28]. There is also criticism that the belief that digital solutions will consistently result in positive sustainability outcomes represents an inherent risk (digital solutionism) [19].…”
Section: De Uplication #And" !$ "! ! Ynthesize Fin Ings An Gapsmentioning
confidence: 99%
See 3 more Smart Citations